Numerical taxonomy of the genus Senna Mill. from Bangladesh - Rahman, M. Oliur; Rahman, Md. Zahidur; Begum, Ayesa (Bangladesh Journal of Plant Taxonomy, 2013)
This study examines the patterns of morphological variation and phenetic relationships among 11 species of Senna Mill. from Bangladesh using 32 vegetative and floral characters. The highest similarity is found between S. obtusifolia and S. tora, while the highest variation is observed between S. alata and S. hirsuta. UPGMA tree derived from cluster analysis reveals three major clusters, the first of which consists of two species (S. alata and S. auriculata), the second cluster comprises four species (S. hirsuta, S. obtusifolia, S. tora and S. occidentalis) and the third one is composed of five species (S. multiglandulosa, S. sophera, S. siamea, S. timoriensis and S. surattensis). A close relationship is also found between S. multiglandulosa and S. sophera, and between S. siamea and S. timoriensis. Results obtained from the present study are found congruent with cytological and anatomical studies showing the significance of numerical analysis for taxonomic relationship in the genus Senna. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15467 Bangladesh J. Plant Taxon. 20(1): 77-83, 2013 (June)